2020
DOI: 10.1055/s-0040-1701206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rivaroxaban on Biomarkers of Coagulation and Inflammation: A Post Hoc Analysis of the X-VeRT Trial

Abstract: Introduction This X-VeRT (eXplore the efficacy and safety of once-daily oral riVaroxaban for the prevention of caRdiovascular events in patients with nonvalvular aTrial fibrillation scheduled for cardioversion) substudy evaluated the effects of treatment with rivaroxaban or a vitamin-K antagonist (VKA) on levels of biomarkers of coagulation (D-dimer, thrombin–antithrombin III complex [TAT] and prothrombin fragment [F1.2]) and inflammation (high sensitivity C-reactive protein [hs-CRP] and high-sensitivity inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 54 publications
1
30
1
Order By: Relevance
“…The anti-inflammatory effect of apixaban was also recently demonstrated in the acute phase of ischemic stroke patients [65]. A post hoc analysis of the X-VeRT trial also revealed that rivaroxaban caused a significant reduction in the levels of D-dimer and IL-6 in patients with atrial fibrillation [66]. These results indicate that blocking the activity of FXa may not only be beneficial to prevent the virus-associated coagulopathies but may also dampen the virus-triggered excessive immune response.…”
Section: Anti-inflammatory Activity Of Direct Fxa Inhibitorsmentioning
confidence: 82%
“…The anti-inflammatory effect of apixaban was also recently demonstrated in the acute phase of ischemic stroke patients [65]. A post hoc analysis of the X-VeRT trial also revealed that rivaroxaban caused a significant reduction in the levels of D-dimer and IL-6 in patients with atrial fibrillation [66]. These results indicate that blocking the activity of FXa may not only be beneficial to prevent the virus-associated coagulopathies but may also dampen the virus-triggered excessive immune response.…”
Section: Anti-inflammatory Activity Of Direct Fxa Inhibitorsmentioning
confidence: 82%
“…In experimental models of myocardial ischaemia–reperfusion injury, the inflammatory response mediated by NF-κB and inflammasome activation was attenuated by inhibition of factor Xa, characterized by the decreased expression of pro-inflammatory mediators 199 . In patients with atrial fibrillation, oral anticoagulation with rivaroxaban or a vitamin K antagonist decreased the levels of IL-6 and C-reactive protein in the plasma 205 . The molecular link for this bidirectional interplay of thrombosis and inflammation might be proteinase-activated receptors (PARs), which self-activate after proteolytic cleavage by serine proteases such as factor X and thrombin 201 .…”
Section: Thromboinflammation As a Therapeutic Targetmentioning
confidence: 97%
“…Taken together, these data demonstrate that patients with AF might benefit from the use of anticoagulants with anti-inflammatory properties. Accordingly, a recent study has demonstrated that the treatment with rivaroxaban (43-98 days, depending on cardioconversion) was associated with reductions in both CRP and IL-6 in comparison with baseline levels (21). However, the evidence is still scarce, and it points out the need for trials seeking to investigate the levels of inflammatory mediators in patients with AF under different anticoagulant therapies.…”
Section: Introductionmentioning
confidence: 99%